xGit2 and xRhoGAP 11A regulate convergent extension and tissue separation in Xenopus gastrulation - Köster, Isabelle; Jungwirth, Maria Sophia; Steinbeisser, Herbert (Developmental biology, 2010)
In a microarray-based screen for genes that are involved in tissue separation downstream of Paraxial Protocadherin (PAPC) and Frizzled-7 (Fz7)-mediated signaling we identified xGit2 and xRhoGAP 11A, two GTPase-activating proteins (GAP) for small GTPases. xGit2 and xRhoGAP 11A are expressed in the dorsal ectoderm, and their transcription is downregulated in the involuting dorsal mesoderm by PAPC and Fz7. Overexpression of xGit2 and xRhoGAP 11A inhibits Rho activity and impairs convergent extension movements as well as tissue separation behaviour. We propose that Rho activity in the involuting mesoderm is enhanced through inhibition of xGit2 and xRhoGAP 11A transcription by PAPC and Fz7. By this mechanism xRhoGAP 11A and xGit2 are restricted to the dorsal ectoderm, while Rho signaling is inhibited.
Gesehen am 21.03.2023